USING SONG TO ENCHANCE LEARNING IN ENGLISH THE CLASSROOM - Pratiwi, Etty (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Abstract— Learning English through songs is one of the best method that the students focus on the lesson better. Because in a song has the variety new words and phrases with many different themes, so the students can learn some items of vocabulary, rhym of language, and grammatical structures that relating to any topic.The fact that English songs for the students are often easy and simple topic that they like most to learn and the students will learn song by hearing it many times, maybe memorization occurs via repetition. Using songs in teaching English is the great way to teach language for students who can not understand fully all the lyric but they still listen to music and sing follow their teacher or music because they are very interesting. However, the teacher should not forget the main purpose that using songs in teaching English is only the tool in order to aim the students in English classroom. In short, I hope that using songs will be effective way for students to enchance learning English and for teachers should choose suitable songs and create various activities to help students learn actively. Keywords— song, enchance learning Abstrak— Belajar Bahasa Inggris melalui lagu adalah salah satu metode terbaik agar siswa fokus pada pelajaran yang lebih baik. Karena dalam sebuah lagu terdapat variasi kata-kata dan frasa baru dengan banyak tema yang berbeda, sehingga para siswa dapat mempelajari beberapa item kosa kata, rhym bahasa, dan struktur gramatikal yang berkaitan dengan topik apa pun. Fakta bahwa lagu-lagu berbahasa Inggris untuk para siswa seringkali mudah dan topik sederhana yang paling mereka sukai untuk dipelajari dan siswa akan belajar lagu dengan mendengarnya berkali-kali, mungkin hafalan terjadi melalui pengulangan. Menggunakan lagu dalam mengajar bahasa Inggris adalah cara terbaik untuk mengajarkan bahasa bagi siswa yang tidak dapat memahami sepenuhnya semua lirik tetapi mereka masih mendengarkan musik dan bernyanyi mengikuti guru atau musik mereka karena mereka sangat menarik. Namun, guru tidak boleh lupa tujuan utama bahwa menggunakan lagu dalam pengajaran bahasa Inggris hanyalah alat untuk membidik siswa di kelas bahasa Inggris. Singkatnya, saya berharap bahwa menggunakan lagu akan menjadi cara yang efektif bagi siswa untuk meningkatkan belajar bahasa Inggris dan untuk guru harus memilih lagu yang sesuai dan membuat berbagai kegiatan untuk membantu siswa belajar secara aktif.. Kata Kunci— lagu, belajar enchance